Evaluation of Salmon (Salmo salar) and Rainbow Trout (Oncorhynchus mykiss) pin bones using textural analysis and micro X-ray computational tomography - Sarah, Schroeder (J Food Sci Technol, 2019)
Industrially, common problems arise with the deboning pin bone process, where Atlantic Salmon (Salmo salar) and Rainbow Trout (Oncorhynchus mykiss) fillets, post rigor, are subjected to a pulling process to remove the pin bones from the fillet. This study measured the length of pin bones from two species of fish and two different industrial graded weights, and then used a texture analyser and µCT X-ray to measure the pulling force, break point and volume of the pin bones of both species of fish. Results showed that salmon pin bones required significantly higher pulling force to remove pin bones from the fish fillet when compared with Trout pin bones. Interestingly Trout pin bones were significantly longer and stronger than Salmon pin bones, but had significantly lower volume. This research has progressed the issues surrounding pin boning industrially, however, more studies are required in order to understand if these differences affect the overall deboning pin bone process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-019-03803-9) contains supplementary material, which is available to authorized users.